2015
DOI: 10.1016/j.biopsycho.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical amplification for emotionally arousing natural scenes: The contribution of luminance and chromatic visual channels

Abstract: Emotionally arousing scenes readily capture visual attention, prompting amplified neural activity in sensory regions of the brain. The physical stimulus features and related information channels in the human visual system that contribute to this modulation, however, are not known. Here, we manipulated low-level physical parameters of complex scenes varying in hedonic valence and emotional arousal in order to target the relative contributions of luminance based versus chromatic visual channels to emotional perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In line with previous studies using this task (Labuschagne et al, 2010; Phan et al, 2008) geometric shapes were used as control stimuli instead of neutral faces, because neutral faces may be more influenced by individual differences (e.g., anxiety levels; Somerville, Kim, Johnstone, Alexander, & Whalen, 2004). Of note, although images were not explicitly matched on perceptual characteristics such as brightness, the LPP has been shown to be relatively “immune” to these effects (Bradley, Hamby, Löw, & Lang, 2007; De Cesarei & Codispoti, 2011; Miskovic et al, 2015). Therefore, although differences in brightness (or other low-level perceptual features) may have modulated early ERPs, it is unlikely that affective modulation of the LPP was attributable solely to these low-level perceptual differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies using this task (Labuschagne et al, 2010; Phan et al, 2008) geometric shapes were used as control stimuli instead of neutral faces, because neutral faces may be more influenced by individual differences (e.g., anxiety levels; Somerville, Kim, Johnstone, Alexander, & Whalen, 2004). Of note, although images were not explicitly matched on perceptual characteristics such as brightness, the LPP has been shown to be relatively “immune” to these effects (Bradley, Hamby, Löw, & Lang, 2007; De Cesarei & Codispoti, 2011; Miskovic et al, 2015). Therefore, although differences in brightness (or other low-level perceptual features) may have modulated early ERPs, it is unlikely that affective modulation of the LPP was attributable solely to these low-level perceptual differences.…”
Section: Methodsmentioning
confidence: 99%
“…Within our a priori regions, there was a positive correlation between fearful > shapes activation in the left Grand-averaged waveforms (at pooling CPz, CP1, CP2, Pz) depicting the LPP for angry, fearful, and happy faces as well as shapes (shown here using a low-pass 12 Hz filter) 3 We did not see evidence of an N170 in the PCA. Additionally, these early components are far more likely to be affected by perceptual differences between faces and shapes De Cesarei & Codispoti, 2011;Miskovic et al, 2015). amygdala and LPP-early-occipital_1 amplitude.…”
mentioning
confidence: 99%
“…The selection of pictures was guided by two considerations: (a) that affective ratings capture one important aspect of the emotional reactivity related to viewing IAPS, but other dimensions such as physiological reactivity tend to capture other, also important, aspects of 1628 D. Kang et al emotional reactivity, sometimes to be balanced against the facets of emotion captured by ratings; and (b) that the overall position of a given picture in the affective space on both dimensions (hedonic valence and emotional arousal) rather than on each dimension was particularly important to us for this study, in which a wide range of contents was targeted rather than relying on narrow content categories. In previous work with this stimulus set, we observed robust separation between categories while maintaining high experimental control (Miskovic et al, 2015), leading us to seek this compromise between clear separation of emotion categories in terms of ratings versus in terms of physiological measures such as the LPP. Hence, replication with a set of pictures showing greater spread between categories in terms of hedonic valence and emotional arousal is desirable.…”
Section: Stimulimentioning
confidence: 99%
“…By contrast, the LPP, a centro-parietal component occurring~300-500 ms poststimulus, signifies allocation of attentional resources for a better, more detailed evaluation of emotional content at a later stage of visual processing (Sabatinelli et al, 2013;Schupp et al, 2000). Despite the close link between attentional orienting toward emotionally significant stimuli and perceptually salient stimulus properties (Bradley, Hamby, Löw, & Lang, 2007;Delplanque, N'diaye, Scherer, & Grandjean, 2007;Miskovic et al, 2015;Schettino, Keil, Porcu, & Müller, 2016), there is mixed evidence regarding whether picture color influences affective processing per se (Cano, Class, & Polich, 2009;Codispoti, De Cesarei, & Ferrari, 2011;Weymar, Löw, Melzig, & Hamm, 2009) and, if so, at which stage of visual processing the influence of color on affective content extraction might be most pronounced. Although two previous studies by Weymar et al (2009) and Codispoti et al (2011) revealed no evidence for an influence of color on heightened visual cortical activity during affective picture viewing, Cano et al (2009) reported ERP emotional modulations late in the processing stream (~300-500 ms) for color but not grayscale pictures.…”
mentioning
confidence: 99%
“…First, confounding effects may have been produced by uncontrolled perceptual stimulus characteristics. Luminance (Miskovic et al, 2015;Schettino et al, 2016), contrast (Kauffmann, Chauvin, Guyader, & Peyrin, 2015), and spatial frequency composition of a visual image Delplanque et al, 2007) have recently been emphasized to modulate behavioral and electrophysiological markers of emotional perception, and were not fully controlled for in those studies. Second, the impact of image color on emotional processing was almost never studied under visually demanding conditions-for example, with very brief image exposure durations.…”
mentioning
confidence: 99%